TUBB3 and KIF21A in neurodevelopment and disease - Puri, Dharmendra; Barry, Brenda J.; Engle, Elizabeth C. (Frontiers in Neuroscience, 2023)
Neuronal migration and axon growth and guidance require precise control of microtubule dynamics and microtubule-based cargo transport. TUBB3 encodes the neuronal-specific β-tubulin isotype III, TUBB3, a component of neuronal microtubules expressed throughout the life of central and peripheral neurons. Human pathogenic TUBB3 missense variants result in altered TUBB3 function and cause errors either in the growth and guidance of cranial and, to a lesser extent, central axons, or in cortical neuronal migration and organization, and rarely in both. Moreover, human pathogenic missense variants in KIF21A, which encodes an anterograde kinesin motor protein that interacts directly with microtubules, alter KIF21A function and cause errors in cranial axon growth and guidance that can phenocopy TUBB3 variants. Here, we review reported TUBB3 and KIF21A variants, resulting phenotypes, and corresponding functional studies of both wildtype and mutant proteins. We summarize the evidence that, in vitro and in mouse models, loss-of-function and missense variants can alter microtubule dynamics and microtubule-kinesin interactions. Lastly, we highlight additional studies that might contribute to our understanding of the relationship between specific tubulin isotypes and specific kinesin motor proteins in health and disease.